The type specimens of sawflies (Hymenoptera: Symphyta) of the Museo Nacional de Ciencias Naturales, Madrid - Taeger, Andreas; París, Mercedes; Nieves-Aldrey, Jose Luis (Zootaxa, 2014)
The type specimens of sawflies (Hymenoptera: Symphyta) housed in the Museo Nacional de Ciencias Naturales, Madrid, were examined. Lectotypes are designated and illustrated for the following 32 nominal taxa (preserved in the MNCN collection if not stated otherwise): Tenthredo acutiscutis Konow, 1908; Tenthredo aericeps Konow, 1907; Allantus albipectus Konow, 1907; Athalia bolivari Dusmet, 1896; Tristactus punctatus var. candidatus Konow, 1899; Tenthredo capistrata Konow, 1907; Megalodontes capitalatus Konow 1904 (coll. SDEI); Tenthredo casta Konow, 1908; Clydostomus cestatus Konow, 1908; Miocephala chalybea Konow, 1907 (coll. SDEI); Peus cupreiceps Konow, 1907; Metallopeus cupreolus Malaise, 1945 (coll. NHRS); Allantus dusmeti Konow, 1894 (coll. SDEI); Megalodontes dusmeti Enslin, 1914 (coll. ZSM); Megalodontes escalerai Konow, 1899; Tenthredo flavitarsis Konow, 1908; Sciopteryx galerita Konow, 1907; Tenthredo habenata Konow, 1907; Allantus inguinalis Konow, 1908; Clydostomus merceti Konow, 1908; Megalodontes merceti Konow 1904 (coll. SDEI); Tenthredo mordax Konow, 1908; Megalodontes mundus Konow, 1904; Tenthredo nimbata Konow, 1906; Tenthredo oculissima Konow, 1907; Peus pannulosus Konow, 1907; Tenthredo podagrica Konow, 1907; Arge segmentaria var. rufiventris Konow, 1899; Tenthredo rugiceps Konow, 1908; Tenthredo segrega Konow, 1908; Peus splendidus Konow 1907; Tenthredo suta Konow, 1906. Peus cupreiceps Konow, 1907, is considered to be a valid species. New synonymy is proposed for Tenthredo (Metallopeus) cupreiceps (Konow, 1907), comb. nov., spec. rev. (=Metallopeus cupreolus Malaise, 1945, syn. nov.; =Metallopeus inermis Malaise, 1945, syn. nov.).